PENGUKURAN NILAI INTANGIBLE PADA PROJECT BASED ORGANIZATION - V. Reza Bayu Kurniawan (Universitas Sarjanawiyata Tamansiswa, 2016)
Intangible factor is a very important factor. The importance of measuring the value of intangible has become a challenge for a company nowadays, not only for functional companies (functional-based organization) but also for project companies (project-based organization). This research aimed to identify intangible factors and measure the value of intangible in organizations which are in the form of project. The value of measured intangible can be used to predict the potential gained value of a project conducted by a company. The object of this research is a project-based company running business on repair and maintenance service (after sale service), logistic, and general contractor (general construction). The identification process of intangible was done by using Analytic Hierarchy Process (AHP) method.Â Then, a prediction model for determining the project value was made by considering its intangible factor. This model was made using multiple-regression analysis. Intangible factors that have been identified are technology, human knowledge, management capability, networking, and financial support. The intangible values of each intangible factor and their qualities respectively are: management capability is 0.444, networking is 0.262, financial support is 0.152, human knowledge is 0.089, and technology is 0.052. From the measured intangible, it can be seen that the value of mean square error (MSE) is 0.0065. It shows that this prediction model can be used to predict a project value by considering its intangible factor